Sedimentary facies and depositional environments of the Halang Formation in the North Serayu Basin: Insights from outcrop study in Bantarbolang, Pemalang, Central Java - Barizi, A.R. Falkhan; Prasetyadi, Carolus; Janukusuma, Miftakhuddin A.S.; Setiawan, M. Nurjati (Berita Sedimentologi, 2024)
Halang Formation has been the subject of extensive research due to its unique characteristics, particularly its turbidite facies, which indicate deposition in deep marine environments. Previous studies have revealed a complex lithological composition, including sandstone, calcareous sandstone, claystone, marl, tuff, and breccia, with an upward coarsening pattern indicative of progradation processes. The presence of Bouma’s sequence further confirms the dominance of turbidite deposits within the formation. This research aims to define the depositional environment of the Halang Formation through detailed lithofacies and microfossil analyses, focusing on a previously understudied area in the North Serayu Basin. By integrating data from field observations and micropaleontological analysis, this study seeks to provide valuable insights into the sedimentary processes and paleoenvironments that formed the Halang Formation. Our findings indicate that the formation was deposited in a submarine fan environment, specifically in the smooth portion of suprafan lobes, which are characterized by dominant classical turbidite (CT) facies. Micropaleontological analysis suggests an inner to outer bathyal environment at depths ranging from 283.65 to 713.7 meters. These results contribute to our understanding of the Halang Formation depositional history and the broader geological evolution of the North Serayu Basin.